Value co-creation between coworking spaces and startups in different stages of development - Barajas, Giuliana; Fleury, André Leme (Revista Gestão da Produção Operações e Sistemas, 2024)
Coworking spaces (CWS) are sustainable pillars for the development of entrepreneurial ecosystems, providing a variety of relevant services, which are co-created in exchanges experienced among different actors. During the pandemic, CWS experienced structural transformations. This study identified, characterised, and evaluated the relevance of the services provided by CWS considering the different stages in the evolution of a startup. For this, a narrative literature review was conducted and the second phase of the research included the development of netnographic initiatives and the conduction of multiple case studies. As a result, six categories of services were identified, comprehending 36 services, whose relevance varies considering the maturity level of the startup. This research contributes to the literature by providing a systemic view of the state of practice of these services in the context of CWS, as well as identifying the changes CWS environments are experiencing driven by digital transformations. Keywords: Coworking Spaces, startup, sharing economy, co-creation, digital transformation.